Age, Gender with Nutritional Status of Renal Failure Patients Undergoing Hemodialysis - Widiastuti, Widiastuti; Khaerunisa, Julia (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Chronic kidney failure is a condition in which structural and functional damage to the kidneys occurs that lasts for 3 months or more. This disease is persistent and cannot be cured, so it requires long-term treatment, such as kidney transplantation, peritoneal dialysis, hemodialysis, and ongoing outpatient therapy. A problem that is often experienced by hemodialysis patients is the nutritional condition of patients with chronic kidney failure, which is influenced by age and gender factors. Purpose: To analyze the relationship between age and sex with nutritional status in chronic kidney failure patients undergoing hemodialysis. Methods: Quantitative method with an analytical observational design and a cross-sectional approach. The study sample consisted of 69 patients with chronic kidney failure. Data analysis was carried out using the Spearman's rho statistical test. Results: Based on the characteristics of male gender respondents as many as 39 respondents (56.5%), with intermediate adult age 41-60 years as many as 38 respondents (55.1%). Conclusion: The results of the study showed that the table of sig values (p-value) = 0.592 and 0.099 or >0.05 showed that there was no significant relationship between age and sex and nutritional status of kidney failure patients undergoing hemodialysis Keywords: Age; Chronic Kidney Failure Patients; Gender; Nutritional Status